Професійна підготовка майбутніх соціальних працівників до мультидисциплінарної взаємодії - Бартків, Оксана (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті проаналізовано зміст підготовки майбутніх соціальних працівників до мультидисциплінарної взаємодії. Відзначено, що однією з технологій сучасної соціально-педагогічної роботи є мультидисциплінарне ведення випадку, яке здійснює команда фахівців різних галузей, з метою надання допомоги клієнту та його оточенню у вирішенні проблем. Професійна підготовка майбутніх соціальних працівників передбачає формування у них системи знань, умінь і навичок міждисциплінарної командної роботи. Змістом навчальних дисциплін «Менеджмент соціальної роботи», «Система організації соціальних служб», «Соціальний супровід сім’ї», «Соціально-педагогічна робота з групами ризику», передбачено формування у майбутніх соціальних працівників умінь працювати в мультидисциплінарній команді та організовувати її роботу; налагоджувати стабільні ділові контакти з фахівцями установ соціальної сфери, з представниками державних і недержавних структур. Охарактеризовано професійні якості, які мають бути сформовані у майбутніх соціальних працівників для успішної роботи в мультидисциплінарній команді. The article analyzes the content of training of future social workers to multidisciplinary interaction. Noted that one of the modern technologies of socio-pedagogical work is multidisciplinary case management, which provides a team of experts from different sectors in order to assist the client and its environment in the solution of problems. Defined the characteristics of a multidisciplinary team: teamwork, the collective work of the team of specialists of different industries; collegiate the development of common approaches, equal consideration of opinions of all experts; interactive process that involves the participation of the client, strict orientation on individual needs of the client. It is noted, that teamwork of specialists in different industries in socio-pedagogical work is a common goal for all its members, however, store personal and individual responsibility of every specialist and shares the volume of activities so that the best use of the capabilities of each participant. Professional training of future social workers involves the formation of knowledge, abilities and skills in multidisciplinary teamwork. The content of training courses "Management of social work", "The system of organization of social services", "Social support of the family", "Socio-pedagogical work with groups risk", forming of future social workers the ability to work in multidisciplinary team and organize its work; to establish stable business contacts with the specialists of social institutions, with representatives of state and non-state actors. Described by a professional quality that should be formed in the future social workers to work in multidisciplinary team.
Keywords: підготовка соціальних працівників; команда; мультидисциплінарна команда; мультидисциплінарне ведення випадку; зміст підготовки соціальних працівників до мультидисциплінарної взаємодії